Language representation and presurgical language mapping in pediatric epilepsy: A narrative review - Karami, Mahdieh; Nilipour, Reza; Barekatain, Majid; Gaillard, William Davis (Iranian Journal of Child Neurology, 2020)
Abstract As one of the most common neurological diseases in children, epilepsy affects 0.9–2% of children. Complex interactions among the etiologies of the epilepsy, interictal discharges, seizures and antiepileptic drugs lead to cognitive impairments in children with epilepsy. Since epilepsy is considered as a network disorder that seizures have widespread impact on many parts of the brain, childhood epilepsy can even affect the normal development of language. About 25% of children with epilepsy do not respond to medications, therefore brain surgery is considered as a treatment option for some of them. Presurgical neuropsychological evaluations including language mapping is recommended to preserve cognitive and language abilities of patients after surgery. Functional magnetic resonance imaging as a non-invasive technique for presurgical language mapping has been widely recommended in many epileptic centers. The present study reviewed language representation and presurgical language mapping in children with epilepsy. In addition, mapping language in children with epilepsy helps to localize epileptogenic zone, to predict cognitive outcome of epilepsy surgery, and possible cognitive rehabilitation. This review gathered information about language representation and language mapping in pediatric epilepsy settings. Key Words: pediatric epilepsy, language development, presurgical evaluation, language laterality